Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar Melalui Penerapan Reward and Punishment di SMP Swasta Nirmala Jopu - Antonios Hubert Esa (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
This study aims to find alternative problem solving as an effort to improve teacher discipline in teaching attendance in class through the application of Reward and Punishment. This research is a classroom action research (CAR) which was carried out in 2 cycles. The subjects of this study were the teachers of SMPK Nirmala Jopu, Wolowaru District, Ende Regency. Based on data analysis, from this study it can be concluded that the application of Reward and Punishment is effective in increasing the discipline of teacher attendance in the classroom in teaching and learning activities. The data obtained shows that after the implementation of actions in the form of Reward and Punishment, teachers who are more than 15 minutes late are 0, and teachers who are less than 10 minutes late are 14 teachers. The application of Reward and Punishment can increase the discipline of the teacher present in the classroom in teaching and learning activities at the Nirmala Jopu Private Junior High School.